Effect of Compression Rate and Pore Size Distribution on the Compression Behavior of Additively Manufactured Bio-inspired Fe3Si Microporous Material - Pramanik, Sudipta; Mileaege, Dennis; Andreiev, Anatolii; Hoyer, Kay-Peter; Schaper, Mirko (Journal of Materials Engineering and Performance)

„Power-Posen“ – Fakten, frisierte Daten, Forschungslyrik? Eine Unterrichtsreihe zu Praktiken und Darstellungsformen psychologischer Forschung - Scharlau, Ingrid; Patrzek, Justine; Schreiber, Christine (Psychologiedidaktik an allgemeinbildenden und beruflichen Schulen: Ein Lehrbuch mit Unterrichtsmaterialien)

Materialien zum Schreiben im Psychologieunterricht - Scharlau, Ingrid; Schreiber, Christine (Psychologiedidaktik an allgemeinbildenden und beruflichen Schulen: Ein Lehrbuch mit Unterrichtsmaterialien)

A Systematic Review of Learning Opportunities within the Crowdworkers’ Workplace - Drechsler, Stephan; Harteis, Christian (Journal of Education and Learning)

"Und es hörten sie die Gefangenen" Eine biblische Gesangsstunde. Apg 16,23-34 (18.5.2025 - Kantate) - Schroeter-Wittke, Harald (Göttinger Predigtmeditationen)

Error estimates for full discretization by an almost mass conservation technique for Cahn--Hilliard systems with dynamic boundary conditions - Bullerjahn, Nils (arXiv)

Modeling reactive absorption in sandwich packings - Franke, Patrick; Schubert, Markus; Hampel, Uwe; Kenig, Eugeny Y. (Proceedings of the Dechema/VDI Jahrestreffen Fluidverfahrenstechnik 2025)

Islam II - Paul, Jürgen; Schneider, Irene; Kokew, Stephan; Malik, Jamal; Schulze, Fritz; Günther, Sebastian; Schrode, Paula; Rebstock, Ulrich; Gharaibeh, Mohammad; Würsch, Renate; Rudolph, Ulrich; Reichmuth, Stefan; et al.

Concepciones de cultura y de encuentros interculturales de futuros/as profesores/as de Alemán como Lengua Extranjera - Treder, Alexandra (Memorias del III Congreso Internacional de Lenguas, Lingüística y Traducción)

Die Sporthalle – Ein Raum zum Sprachenlernen? Zwischen der Forderung nach Integration durch Sport und Sprache(n) als Schlüssel zur Integration - Treder, Alexandra (Transdisziplinäre Räume in den Kulturwissenschaften)

„Alles was gut ist“ – Jan Wagners lyrische Speisen (mit Getränken) - Elit, Stefan (Was im Gedicht geschieht: Jan Wagner. Paderborn Wintersemester 2023/2024)

Multiphoton, multimode state classification for nonlinear optical circuits - Kopylov, Denis; Offen, Christian; Ares, Laura; Wembe Moafo, Boris Edgar; Ober-Blöbaum, Sina; Meier, Torsten; Sharapova, Polina; Sperling, Jan
We introduce a new classification of multimode states with a fixed number of photons. This classification is based on the factorizability of homogeneous multivariate polynomials and is invariant under unitary transformations. The classes physically correspond to field excitations in terms of single and multiple photons, each of which being in an arbitrary irreducible superposition of quantized modes. We further show how the transitions between classes are rendered possible by photon addition, photon subtraction, and photon-projection nonlinearities. We explicitly put forward a design for a multilayer interferometer in which the states for different classes can be generated with state-of-the-art experimental techniques. Limitations of the proposed designs are analyzed using the introduced classification, providing a benchmark for the robustness of certain states and classes.

Pädagogik und Sexualität. Analysen eines Konfliktfelds.

Gaia-X in industriellen Wertschöpfungsnetzwerken – Erkenntnisse aus der Förderlinie InGAIA-X - Dumitrescu, Roman; Riedel, Oliver; Henke, Michael; Metternich, Joachim; Ihlenfeldt, Steffen; Koldewey, Christian
Die Publikation richtet sich an Industrieunternehmen und Forschende, die an der Nutzung von Gaia-X für die industrielle Produktion interessiert sind. Sie vereint die Ergebnisse der Forschungsprojekte COSMIC-X, DIONE-X, Fed-X-Pro, GRIPSS-X und URANOS-X, die zur Entwicklung von Anwendungsszenarien für Gaia-X-konforme Datenökosysteme beigetragen haben. Ziel ist es, insbesondere mittelständische Unternehmen in die Lage zu versetzten, souverän Datenräume zu nutzen, um die digitale Transformation voranzutreiben und ihre Wettbewerbsfähigkeit zu steigern. Wichtige Technologien sind dabei Blockchain, Self-Sovereign Identity (SSI) und die Asset Administration Shell (AAS). Die Projektergebnisse stärken die Innovationskraft und eröffnen neue Geschäftsmodelle in der Industrie 4.0. Inhaltsverzeichnis Abstract VII 1 Einleitung 1 1.1 Gaia-X – Chance fur die industrielle Produktion . . . . . . . . . . . . . . . ü 1 1.1.1 Mü oglichkeiten von Gaia-X in der industriellen Produktion . . . . . 4 1.1.2 Die aktuelle Projektlandschaft . . . . . . . . . . . . . . . . . . . . . 7 1.2 Die InGAIA-X Fü orderlinie . . . . . . . . . . . . . . . . . . . . . . . . . . . 8 1.2.1 Die Projekte . . . . . ...

Enhancing SME Resilience through Artificial Intelligence and Strategic Foresight: A Framework for Sustainable Competitiveness - Carayannis, Elias G.; Dumitrescu, Roman; Falkowski, Tommy; Papamichail, George; Zota, Nikos - Rigert (Technology in Society)

Annaberg, Marienberg, Potosí. Neue Städte in Silberbergbauregionen der Frühen Neuzeit - Silvestri, Marco

Das unkaputtbare Patriarchat? Geschlechterhierarchie als Gegenstand erziehungswissenschaftlicher Frauen- und Geschlechterforschung.

Mee To in Science. Sexualisierte Diskriminierung und Gewalt an Hochschulen.

Quantum-Classical Correspondences for Locally Symmetric Spaces - Hilgert, Joachim (Symmetry in Geometry and Analysis, Volume 2)

Flight due to climate change in Jostein Gaarder’s novel 2084: Noras’s World - Jagdschian, Larissa Carolin (Filoteknos: Migration Narratives: Staying, Leaving, and Returning in Children's and Young Adult Literature)